Explaining Entrepreneurial Status and Success from Personality: An Individual-Level Application of the Entrepreneurial Orientation Framework. Issue 1 (4th June 2015) - Vantilborgh, Tim; Joly, Jeroen; Pepermans, Roland
Entrepreneurial orientation is defined as an organization's strategy, describing its innovativeness, proactivity, risk taking, autonomy and competitiveness. We argue that this concept can be translated to the individual level as a constellation of five personality traits that characterize entrepreneurs. We examine the usefulness of these five traits in explaining entrepreneurial status and success. Our results show that entrepreneurs score higher than non-entrepreneurs on innovativeness, proactivity, and risk taking. In addition, latent growth curve modeling revealed that the individual EO traits were related to objective venture performance, albeit only after introducing venture life cycle as a moderator. In line with a differentiation perspective, risk taking, innovativeness, need for achievement, and need for autonomy were positively related to revenue and number of employees when venture life cycle was high. In line with a situation strength perspective, need for autonomy was positively related with growth in number of employees when venture life cycle was low. We conclude that individual entrepreneurial orientation offers a useful framework to understanding entrepreneurship once situational factors, such as venture life cycle, are taken into consideration.